The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1002/smj.2695
|View full text |Cite
|
Sign up to set email alerts
|

Do ongoing networks block out new friends?Reconciling the embeddedness constraint dilemma on new alliance partner addition

Abstract: Research Summary: This study addresses a theoretical dilemma regarding how alliance network constraint (reflected by network cohesion) affects a firm's alliance formation with new partners. Using a network pluralism approach, we separate a firm's ego alliance network into two activity-based networks-an exploratory network and an exploitative network-based on the primary value chain activity involved in each alliance. We argue that the cohesion of exploratory or exploitative networks has an inverted U-shaped ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 133 publications
(203 reference statements)
0
58
1
Order By: Relevance
“…At the same time, embeddedness may constrain the new relationships that an organization can form (Jiang, Xia, Cannella, & Xiao, 2018). A charity's political ties can give rise to concerns and risks for donors.…”
Section: Political Embeddedness As a Liabilitymentioning
confidence: 99%
“…At the same time, embeddedness may constrain the new relationships that an organization can form (Jiang, Xia, Cannella, & Xiao, 2018). A charity's political ties can give rise to concerns and risks for donors.…”
Section: Political Embeddedness As a Liabilitymentioning
confidence: 99%
“…We expect new partner inflow will negatively influence firm performance. First, from a resource flow perspective, although external new partners bring novel and non-redundant resources into the alliance portfolio [12], the acquisition and utilization of these resources are challenges for the firm [42]. On the one hand, the novel and non-redundant resources possessed by the new partner may not match the existing resources of the alliance portfolio in the short term [43].…”
Section: The Performance Consequence Of Alliance Partner Reconfigurationmentioning
confidence: 99%
“…As changes occur in the external or internal environment, firms continuously re-structure the partner composition of their alliance portfolio based on the last alliance portfolio [8,11]. Previous work has found that alliance partners frequently undergo significant change over a firm's life [12,13]. Due to the need for complementary partner resources and stable cooperative relationships, a partner may enter the alliance portfolio or leave it.…”
Section: Introductionmentioning
confidence: 99%
“…Wassmer and Madhok based on data from the global aviation industry, found that resource balance at the portfolio level helps airlines to improve performance, and pointed out that managers should be careful to obtain excessive resources through a few partners [17]. Jiang et al studied how network constraints (network cohesion) of the alliance affect a company's alliance with new members and found that when a company's alliance members are closely connected to each other, a cohesive network often encourages and hinders the company from adding new alliance members [18].…”
Section: Strategic Alliancementioning
confidence: 99%